Patricians and Popolani : The Social Foundations of the Venetian Renaissance State - Romano, Dennis, 1951- (Book collections on Project MUSE., 2019)
Community and conflict in early Renaissance : Family structure and marriage ties : The world of work : guild structure and artisan networks : The parochial clergy and communities of the sacred.